2017
DOI: 10.1177/1744806917716234
|View full text |Cite
|
Sign up to set email alerts
|

Epac and nociceptor sensitization

Abstract: Primary sensory neurons are responsible for transmitting sensory information from the peripheral to the central nervous system. Their responses to incoming stimulation become greatly enhanced and prolonged following inflammation, giving rise to exaggerated nociceptive responses and chronic pain. The inflammatory mediator, prostaglandin E2 (PGE2), released from the inflamed tissue surrounding the terminals of sensory neurons contributes to the abnormal pain responses. PGE2 acts on G protein-coupled EP receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
1
19
0
Order By: Relevance
“…Because we did not detect a role for PKA we also investigated two additional proteins that can respond to increased levels of cAMP and mediate downstream signaling responses (see Figure 1B ); EPAC1/Rapgef1 (inhibited by ESI09) and EPAC2/Rapgef2 (inhibited by SQ22,536). Downstream targets of EPAC1 1 and 2 include ERK and PKC respectively ( Huang and Gu, 2017 ). However, inhibition of EPAC1 with ESI09 did not inhibit forskolin-mediated reactivation ( Figure 2—figure supplement 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Because we did not detect a role for PKA we also investigated two additional proteins that can respond to increased levels of cAMP and mediate downstream signaling responses (see Figure 1B ); EPAC1/Rapgef1 (inhibited by ESI09) and EPAC2/Rapgef2 (inhibited by SQ22,536). Downstream targets of EPAC1 1 and 2 include ERK and PKC respectively ( Huang and Gu, 2017 ). However, inhibition of EPAC1 with ESI09 did not inhibit forskolin-mediated reactivation ( Figure 2—figure supplement 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Two variants, Epac1 and Epac2, couple cAMP to activate Rap, through which cAMP influences diverse cellular processes (Holz et al., ) including exocytosis or externalization (Bos, ). Recent evidence showed that cAMP/Epac signalling plays an important role in chronic pain by sensitizing nociceptors (Singhmar et al., ; Huang and Gu, ; Matsuda et al., ) cAMP/Epac has been shown to mediate numerous functions of EP4 activation (Yokoyama et al., ). In the present study, we found that cAMP/Epac activator 8‐pCPT in a concentration‐dependent manner increased EP4 externalization, suggesting that in parallel with cAMP/PKA, cAMP/Epac signalling is also involved in agonist‐induced EP4 externalization.…”
Section: Discussionmentioning
confidence: 99%
“…Intraplantar injection of the EPAC agonists led to long‐lasting mechanical hyperalgesia (Hucho et al, ). Moreover, the expression of EPAC1 and EPAC2 markedly increased at the time when nociceptive hypersensitivity developed after plantar incision (Huang & Gu, ; Mizukoshi et al, ). Particularly interesting, genetic deletion of EPAC1 protected against inflammation‐induced mechanical hyperalgesia, whereas selective EPAC1 inhibition prevented or reversed existing inflammation or incision‐induced nociceptive hypersensitivity without affecting normal pain sensitivity (Hucho et al, ; Singhmar et al, ).…”
Section: Discussionmentioning
confidence: 99%